Antinociceptive action of Light Emitting Diode in an experimental model with hyperalgesia by capsaicin - Kerppers,Ivo Ilvan (2014)
OBJECTIVE: To assess the antinociceptive effect of a light emitting diode (LED) in the acute phase of pain induced by capsaicin. METHOD: Twelve Wistar rats were used, divided into a control and an experimental group. The pain process was induced in both groups by applying 50 microliters of a 2% capsaicin solution in the plantar region of the right hind limb. In the experimental group, a single application of LED 627nm (70mw, 7 Joules/cm2 dose) was also applied. Nociception was assessed 30 minutes and 24 hours after LED application using a digital analgesymeter (Von Frey). RESULTS: Twenty four hours after irradiation, an increase in the nociceptive threshold was observed in the LED group in comparison to the 30 min level, as well as in the inter-group comparison. CONCLUSIONS: The use of LED can be considered as a non-invasive analgesic method as it increases of the nociceptive threshold 24 hours after pain is induced.